P134Increased beta-adrenergic inotropy in ventricular myocardium from Trpm4 knockout mice. (15th July 2014) - Kecskes, M; Mathar, I; Griet, J; Van Der Mieren, G; Voets, T; Herijgers, P; Vennekens, R
Abstract: TRPM4 have an extensive role in regulating intracellular calcium dependent cell functions in many cells including mast cells, chromaffin cells and recently in neurons. TRPM4 proteins constitute calcium activated, but calcium impermeable, non-selective cation channels and are expressed both in atrial and ventricular cardiomyocytes. The Trpm4 gene has recently been associated with several disorders, including cardiac conduction diseases such as Progressive Familial Heart Block Type 1, Right Bundle Branch Block and Brugada Syndrome. The physiological function of TRPM4 in the heart remains however incompletely understood. The objective of this study was to establish the role of TRPM4 in left ventricular muscle function. We used TRPM4 knockout mice and performed patch-clamp experiments, membrane potential measurements, microfluorometry, contractility measurements and in vivo pressure-volume loop analysis. We demonstrate that TRPM4 proteins are functionally present in mouse ventricular myocytes and are activated upon calcium induced calcium release. Measurements of action potential duration show that TRPM4 is active during the repolarization of the ventricular action potential. We show a significantly decreased time for 50 % and 90 % repolarization in Trpm4 knockout ventricular myocytes. We also provide evidence that this change in action potential shape leads to an increased driving force for the L-type calcium current during the action potential. Moreover, in vivo pressure-volume analysis and in vitro contraction strength measurement on isolated papillary muscles displays an increased β-adrenergic inotropic response in TRPM4 knockout mice. Taking together these data, our results show that functional TRPM4 proteins are novel determinants of the inotropic effect of β-adrenergic stimulation on the ventricular heart muscle.